2020
DOI: 10.1016/j.scitotenv.2020.141322
|View full text |Cite
|
Sign up to set email alerts
|

Early spring near-surface ozone in Europe during the COVID-19 shutdown: Meteorological effects outweigh emission changes

Abstract: This paper analyses the impact of the control measures during the COVID-19 lockdown in Europe (15 March–30 April 2020) on 1-h daily maximum nitrogen dioxide (NO 2 ) and maximum daily 8-h running average ozone (MDA8 O 3 ) observations obtained from the European Environment Agency's air quality database (AirBase). Daily maximum NO 2 decreased consistently over the whole continent, with relative reductions ranging from 5% to 55% with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
108
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 56 publications
(71 reference statements)
23
108
2
2
Order By: Relevance
“…In addition to these pollutants, the meteorological parameters also play an important role in the production of ozone. Advection of warm and polluted air masses can also raise the near surface ozone concentrations ( Sun et al, 2017 ; Garrido-Perez et al, 2019 ; Ordonez et al, 2020 ). Higher temperatures and stagnant conditions at Delhi and Kolkata are likely to have favored the photochemical reactions and increase the production rates of O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these pollutants, the meteorological parameters also play an important role in the production of ozone. Advection of warm and polluted air masses can also raise the near surface ozone concentrations ( Sun et al, 2017 ; Garrido-Perez et al, 2019 ; Ordonez et al, 2020 ). Higher temperatures and stagnant conditions at Delhi and Kolkata are likely to have favored the photochemical reactions and increase the production rates of O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…China: (Agarwal et al, 2020;Chauhan and Singh, 2020;Chen et al, 2020a;Chen et al, 2020c;Chen et al, 2020d;Fan et al, 2020;G Huang and Sun, 2020;Lian et al, 2020;Liu et al, 2020c;Miyazaki et al, 2020;Nichol et al, 2020;Pei et al, 2020;Shakoor et al, 2020;Shi and Brasseur, 2020;Silver et al, 2020;Wan et al, 2020;Wang et al, 2020a;Wang et al, 2020b;Wang et al, 2020f;Xu et al, 2020c;Zhang et al, 2020a;Yuan et al, 2021) Other: (Ghahremanloo et al, 2020;Han et al, 2020;Ju et al, 2020;Ma and Kang, 2020;Zhang et al, 2020b) South Asia India: (Bedi et al, 2020;Beig et al, 2020;Biswal et al, 2020;Chatterjee et al, 2020;Gautam et al, 2020;Harshita and Vivek, 2020;Jain and Sharma, 2020;Kant et al, 2020;Kumari and Toshniwal, 2020;Panda et al, 2020;Ranjan et al, 2020;Selvam et al, 2020;Sharma et al, 2020a;Siddiqui et al, 2020;Singh and Chauhan, 2020;…”
Section: East Asiaunclassified
“…,,(Le et al, 2020a), a(Lian et al, 2020) a ,(Liu et al, 2020a),(Ma and Kang, 2020), a(Metya et al, 2020),(Nichol et al, 2020), a (Pei et al, 2020), a (Shakoor et al, 2020), a (Shi and Brasseur, 2020), a (Silver et al, 2020), (Venter et al, 2020), (Wang et al, 2020b), a (Xu et al, 2020c), a (Zhang et al, 2020a), a (Zhang et al, 2020c), (Zhao et al, 2020b), a (Zheng et al, 2020), (Wang et al, 2020e), a (Fu et al, 2020), (Wang et al, 2020f), a (Wang et al, 2020a), a (Ding et al, 2020), (Chen et al, 2020d), a (Ghahremanloo et al, 2020), (Zhang et al, 2020d), (Fan et al, 2020), a (Wan et al, 2020), a (Xu et al, 2020c), a (Yuan et al, 2021), a…”
mentioning
confidence: 99%
“…For these and other reasons related to geography, weather, and sources, ozone has become one of the most difficult pollutants to control in megacities. An example of this is that, despite the confinement carried out around the world due to COVID-19 sanitary crisis, reports indicate that, in many cities, ozone levels did not drop as expected, while several other cities reported an increase in ozone concentrations, such as Rio de Janeiro [12] and cities in Great Britain, France, Germany, and Italy [13,14], and China [15], all of them with a VOC-limited regime. Those reports suggested that the main reason for this increase is the important decrease in NOx raising ozone accumulation.…”
Section: Introductionmentioning
confidence: 95%